Estudo comparativo da marcha de indivíduos hemiparéticos no solo e na esteira - Mendes, Luciana de Andrade (2009)
The purpose of the study was to compare hemiparetic gait overground and on the treadmill. Seventeen chronic stroke patients were included in the study. They walked overground and on a treadmill level at the same speed. The Qualisys Medical AB motion analysis system was used to quantify the joint kinematic of the paretic lower limb and the spatio-temporal parameters on the two conditions: overground walking and treadmill walking on three samples of 5-minutes. During the first sample, the subjects walked on the treadmill with greater cadence, shorter stride length, shorter step time on the lower paretic limb, greater range of motion in the hip and knee, greater knee flexion at the initial contact, more extension of the knee and lower dorsiflexion of the ankle at the stance phase. It is important to emphasize that the maximal knee flexion and ankle dorsiflexion just occurred later on the treadmill. Comparisons between each walking sample on the treadmill hadn t revealed any changes on the gait parameters over time. Nonetheless, when analyzing the third walking sample on the treadmill and overground, some variables showed equivalence as such as the total range of motion of the hip, the knee angle at the initial contact and its maximal extension at the stance phase. In summary, walking on a treadmill, even thought having some influence on the familiarization process, haven t demonstrated a complete change in its characteristics of hemiparetic chronic patients